Presentation: To listen with your body - Ahlstrand, Pernilla (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2016)
This is the (slightly revised) english summery attatched in the dissertation »Att kunna lyssna med kroppen. En studie av gestaltande förmåga inom gymnasieskolans estetiska program, inriktning teater« (Ahlstrand 2014). The full version of the dissertation can be read online.